1982
DOI: 10.1007/bf00345492
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum glutamate in depressed patients

Abstract: Glutamate concentration was determined in serum from endogenous and neurotic depressive patients, in persons with schizophrenia or schizoaffective disorder, and in normal subjects. The mean serum glutamate level in the endogenous and neurotic depressive patients was found to be significantly higher than in any of the other groups. No other statistically significant differences were found. Statistical analysis revealed that the elevated serum glutamate concentration in the endogenous and neurotic depressive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(72 citation statements)
references
References 16 publications
1
68
0
3
Order By: Relevance
“…Most studies focused on peripheral glutamate levels in people with Sz. In a metaanalysis [86] of 10 studies, higher levels (standardized mean difference = 0.64; 95%CI = 0.21-1.06) of glutamate have been reported in blood from people with Sz compared to controls, however, similar dysregulations have been reported in the small number of studies that focused on major depressive disorder [90,91] , suggesting the alteration of glutamate levels is not specific to the diagnosis of Sz. Interestingly, the response of platelet intracellular calcium to glutamate was greater in people with Sz than in controls, suggesting NMDA receptor may be more sensitive in these people [87] .…”
Section: Glutamatergic Pathwaysmentioning
confidence: 99%
“…Most studies focused on peripheral glutamate levels in people with Sz. In a metaanalysis [86] of 10 studies, higher levels (standardized mean difference = 0.64; 95%CI = 0.21-1.06) of glutamate have been reported in blood from people with Sz compared to controls, however, similar dysregulations have been reported in the small number of studies that focused on major depressive disorder [90,91] , suggesting the alteration of glutamate levels is not specific to the diagnosis of Sz. Interestingly, the response of platelet intracellular calcium to glutamate was greater in people with Sz than in controls, suggesting NMDA receptor may be more sensitive in these people [87] .…”
Section: Glutamatergic Pathwaysmentioning
confidence: 99%
“…NMDA receptor antagonists increase the serotonin levels in the brain. 20,21 Several studies showed an increased activity of the glutamatergic system in the peripheral blood of depressive patients, [22][23][24] although this result could not be replicated by all authors. 25 The inconsistency of the findings, however, might be due to medication effects, low statistical power and a lack of appropriate control of diagnosis.…”
Section: Glutamate In Depressionmentioning
confidence: 99%
“…Blood glutamate levels have been shown to increase in medicated patients [61,62]. Mitani et al [63] reported that increased glutamate plasma levels reflected the severity of depression.…”
Section: Role Of Glutamatergic Transmission In Depressionmentioning
confidence: 99%